2011
DOI: 10.1038/srep00115
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Scattering Studies of spin excitations in hole-doped Ba0.67K0.33Fe2As2 superconductor

Abstract: We report inelastic neutron scattering experiments on single crystals of superconducting Ba0.67K0.33Fe2As2 (Tc = 38 K). In addition to confirming the resonance previously found in powder samples, we find that spin excitations in the normal state form longitudinally elongated ellipses along the QAFM direction in momentum space, consistent with density functional theory predictions. On cooling below Tc, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 43 publications
5
65
0
Order By: Relevance
“…Recent neutron scattering experiment on the same batch of Ba 0.67 K 0.33 Fe 2 As 2 crystal revealed that the low-energy spin excitations below T c displays a sinusoidal modulation, indicating clear gap at momentum transfer q z =0 but gapless behavior at q z =π. 8 Presence of nodes in different regions of FSs was also suggested in theoretical studies, including nodes on 2D electron type FSs near the zone corner 31 , vertical and small segment nodal lines on the 3D hole FS and horizontal nodes on the 3D FS 32 . As we elaborated above, the c-axis optical measurement mainly probes the 3D FS, while the nodes on the 2D electron FSs would have strong effect on the in-plane conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Recent neutron scattering experiment on the same batch of Ba 0.67 K 0.33 Fe 2 As 2 crystal revealed that the low-energy spin excitations below T c displays a sinusoidal modulation, indicating clear gap at momentum transfer q z =0 but gapless behavior at q z =π. 8 Presence of nodes in different regions of FSs was also suggested in theoretical studies, including nodes on 2D electron type FSs near the zone corner 31 , vertical and small segment nodal lines on the 3D hole FS and horizontal nodes on the 3D FS 32 . As we elaborated above, the c-axis optical measurement mainly probes the 3D FS, while the nodes on the 2D electron FSs would have strong effect on the in-plane conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…The BFA and BKFA samples used in our RIXS experiments are single crystals grown using the self-flux method 22,23 . Resistivity and bulk magnetic susceptibility measurements demonstrate the high quality of all samples (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The high-quality single crystals of BFA and BKFA used in the current study were grown by the flux method as described in Chen et al 22 and Zhang et al 23 High-resolution RIXS experiments were performed using the SAXES spectrometer at the Advanced Resonant Spectroscopy (ADRESS) beamline of the Swiss Light Source, Paul Scherrer Institut, Switzerland. The energy and momentum resolutions were 40 meV (HWHM) and 0.01 Å À 1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…the anisotropy is opposite and J 1 is AFM for the iron-based compounds. It is interesting to note that the spin fluctuation anisotropy is predicted to become negative (η < 0) in hole-doped AFe 2 As 2 [16], which has subsequently been observed in Ba 1−x K x Fe 2 As 2 [17].…”
Section: Figures 1(a) -(E)mentioning
confidence: 99%